Analisis Studi Kelayakan Bisnis Freshcake Rohmawati: Tinjauan Aspek Legalitas, Sistem Pemasaran, Dan Keuangan - Daimah Dianawati; Ami Nurhidayah; Dwi Astuti (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to analyze the feasibility of Rohmawati's Freshcake business based on legal, marketing and financial aspects. Freshcake Rohmawati, as one of the MSMEs in Bekasi Regency, presents typical cake products with an innovative digital-based strategy. A qualitative approach was used by collecting data through interviews, observation and document study. The research results show that the legality aspects of the business include NIB and PIRT certificates, but have not yet obtained MUI halal certification and trademark registration, which have the potential to add to the legal basis of the business. In marketing, the use of social media is quite effective in increasing market awareness, but does not make optimal use of digital campaign strategies, such as collaboration with influencers or development of official websites. In the financial aspect, transaction recording is still done manually, so cash flow is difficult to monitor, and evaluation of profit margins is not routine. Strategy recommendations include prioritizing halal certification and trademark management, optimizing digital marketing through social media and marketplace collaboration, as well as implementing simple financial recording technology such as the BukuKas application. Through these steps, Freshcake Rohmawati is expected to be able to increase business appetite and have a positive impact on the local economy. These findings are also relevant for other MSMEs in facing similar challenges in the era of business digitalization.